Evaluation of Industry 4.0 practices within retail sector in the Czech Republic - Sahánek, Radovan; Tyll, Ladislav; Jirsák, Petr; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2019)
This thesis aims to evaluate the relevance of Industry 4.0 practices within the retail sector in Czechia and uncover Czech retail specifics related to Industry 4.0. To achieve the aim, the thesis provides a comprehensive overview of the global retail sector and related trends based on academic papers, professional studies and company reports. The concept of Industry 4.0 is introduced, together with the description of the industrial revolutions, Industry 4.0 ecosystem and selected technologies. The key part of the paper forms qualitative research. Semi-structured interviews with respondents from 8 retail companies were conducted to answer 6 research questions to evaluate the current dynamics of Czech retail sector in relation to Industry 4.0. The outcomes of the thesis suggest that Czech retailers are familiar with the term, but its concepts are more understood within the supply chain area. Retailers have mixed feelings about Industry 4.0 and are often sceptical about its business benefits. Considering the omnichannel trend, there are indications that the activity towards Industry 4.0 will be growing.
Vedoucí práce: Ladislav Tyll
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2019
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2019
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses